Development Of The Inclusive Education System. - Karimova Shoira Bakhtiyorovna (Periodica Journal, 2025)
This article focuses on solving the problems of education of individuals in need of special attention. Among children in need of special assistance, the development of the inclusive education system is discussed, namely, children who are deprived of hearing to a certain extent
Keywords: Inclusive; education; correction